Simulating enzyme reactivity - Tuñón, Iñaki; Moliner, Vicent (RSC theoretical & computational chemistry series, 2017)
Exploring the theories, methodologies and applications in simulations of enzymatic reactions, this book is a great resource for postgraduate students and researchers